Effect of Chromium-Doping on the Crystallization and Phase Stability in Anodized TiO2 Nanotubes - Low, It Meng; Albetran, Hani; Prida, Victor; Manurung, P; Ionescu, M (Wiley, 2012)
Production of limitless hydrogen fuel by visible light splitting of water using the photo-electrochemical technology is cost-effective and sustainable. To make this an attractive viable technology will require the design of TiO2 photocatalyst capable of harnessing the energy of visible light. One possible solution is the doping of TiO2 to reduce its band gap. In this paper, the effect of Cr-doping by ion-implantation on the crystallisation and phase stability of TiO2 nanotubes at elevated temperature is described. The effect of Cr-doping on the resultant microstructures, phase changes and composition depth profiles are discussed in terms of synchrotron radiation diffraction, scanning electron microscopy, and ion-beam analysis by Rutherford backscattering spectrometry.